Respiratory Physiotherapy and COVID-19 - Jorge Luis Abreus Mora; Vivian Bárbara González Curbelo (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Physiotherapy is an integral part of intensive care management. Respiratory physiotherapy is considered one of the therapeutic options for the relief of symptoms in various respiratory viral infections, including COVID-19. COVID-19 infection significantly increased the risk of mortality and the burden of disability for most survivors. The rehabilitation needs of infected people should be a priority in the care of these patients. Physiotherapy is presented as a prophylactic and therapeutic strategy for the treatment of this condition. Early interventions, including exercise and mobilization, help reduce the severity of associated complications and facilitate functional recovery after the acute phase.